Constructing The European Education Space - Besgul, Ozge Onursal (Uluslararasi Iliskiler Konseyi Dernegi, 2012)
This study analyses the European education policy and traces its evolution, specifically focusing on the Bologna Process that was launched in 1999. The study aims mainly at answering the following two questions: How is the European education space constructed and on which narrative is it built upon? In answering these questions, the article also discusses how the concept of European citizenship is defined in educational documents. The paper argues that the narrative of education policy initially had a regional focus, which later gained an international dimension.
Keywords: Eu Education Policy; Education Space; Bologna Process; Eu Citizenship